Implementation of the Competition Method in Improving Student Understanding in Islamic Cultural History Lessons at MTs Negeri 12 Indramayu - Carsinih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to explore the nature of the implementation of the competition method in improving students' understanding of SKI learning. This study uses a qualitative approach with a case study type on the use of the competitive method at MTs Negeri 12. The results of the study indicate that the competition method in learning is a method that can provide a positive influence on a conducive, interesting and enjoyable learning atmosphere. In addition, this study also found that the competition method in learning has a philosophical value that is in accordance with the spirit of Islamic teachings, namely competing in goodness. Overall, the competition method can change students' mindsets in learning, raise students' enthusiasm in learning, foster a sporty and honest attitude and personality. In other words, this competition method is very influential on the student learning process at school. The teacher is only an intermediary for students, and the rest is the students who determine their own future.